The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1016/j.jacc.2004.10.066
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of transcatheter secundum-type atrial septal defect closure using Amplatzer septal occluders

Abstract: Since the first human implantations in September 1995, the Amplatzer septal occluder proved as a safe and effective device for percutaneous closure of ASD II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
128
0
9

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(140 citation statements)
references
References 17 publications
3
128
0
9
Order By: Relevance
“…Several studies and our own experience have demonstrated clinical benefits and positive right-heart remodeling, with reduction of the right ventricular end-diastolic diameter. (8)(9)(10)(11)(12)(13)(14)(15)(16)(17) However, few studies were published considering geriatric patients, who older than 70 years. (18)(19)(20)(21) In this aged population, not only catheter closure of ASD but also surgical closure has been reported very limited experiences, little data are published on functional results.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies and our own experience have demonstrated clinical benefits and positive right-heart remodeling, with reduction of the right ventricular end-diastolic diameter. (8)(9)(10)(11)(12)(13)(14)(15)(16)(17) However, few studies were published considering geriatric patients, who older than 70 years. (18)(19)(20)(21) In this aged population, not only catheter closure of ASD but also surgical closure has been reported very limited experiences, little data are published on functional results.…”
Section: Introductionmentioning
confidence: 99%
“…The procedure presents a low rate of hospital complications, reduced hospital stays and safety, based on late follow-up [26][27][28] . Besides the device's proven safety, the transcatheter procedure avoids a thoracotomy and offers the benefit of not submitting the patient to aortic clamping and extracorporeal circulation, crucial timeframes in atrioseptoplasty.…”
Section: Resultsmentioning
confidence: 99%
“…2 Masura and colleagues reported no re-interventions during their median follow-up of 78 months. 20 Takaya and colleagues reported no procedure-related complications during a median follow-up of 36 months. 21 Those findings show the safety and effectiveness of transcatheter ASD closure, which has become the new standard treatment for the ostium secundum type of ASD.…”
Section: Study Limitationsmentioning
confidence: 98%
“…17, 18 Recent studies have reported that the procedural mortality is nearly zero and the rate of successful closure is greater than 95%. 3,19, 20 In terms of long-term outcomes, Kotowycz and colleagues reported a 5-year re-intervention rate of 7.9% and 5-year mortality rate of 5.3%. 2 Masura and colleagues reported no re-interventions during their median follow-up of 78 months.…”
Section: Study Limitationsmentioning
confidence: 99%